2021
DOI: 10.1038/s41598-021-88867-4
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Morpho-molecular identification and first report of Fusarium equiseti in causing chilli wilt from Kashmir (Northern Himalayas)

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The macroconidia had 3-4 septate hyaline parts and sizes of 21-28 × 3.8-4.5 µm. Hami et al (2021) observed that F. solani mycelium was smooth, cylindrical, branched, and septate. The conidiophores measured 88.60-110.50 × 2.5-4.50 µm in size and were cylindrical and septate.…”
Section: Discussionmentioning
confidence: 99%
“…The macroconidia had 3-4 septate hyaline parts and sizes of 21-28 × 3.8-4.5 µm. Hami et al (2021) observed that F. solani mycelium was smooth, cylindrical, branched, and septate. The conidiophores measured 88.60-110.50 × 2.5-4.50 µm in size and were cylindrical and septate.…”
Section: Discussionmentioning
confidence: 99%
“…These OTUs belong to known plant pathogens: Fusarium equiseti , Fusarium oxysporum , Fusarium solani , Fusarium sp. ( Zhang et al, 2006 ; Michielse and Rep, 2009 ; Hami et al, 2021 ). Statistical analysis showed significative reduction only for OUT6 and OTU10.…”
Section: Discussionmentioning
confidence: 99%